The 3rd selection is appropriate.
.. 5b +1 = a = 3b +5
by the transitive property of equality,
.. 5b +1 = 3b +5
Answer:
Step-by-step explanation:
a).
= ![\frac{5}{3}\pm \frac{\sqrt{-4}}{3}](https://tex.z-dn.net/?f=%5Cfrac%7B5%7D%7B3%7D%5Cpm%20%5Cfrac%7B%5Csqrt%7B-4%7D%7D%7B3%7D)
= ![\frac{5}{3}\pm\frac{2\sqrt{(-1)} }{3}](https://tex.z-dn.net/?f=%5Cfrac%7B5%7D%7B3%7D%5Cpm%5Cfrac%7B2%5Csqrt%7B%28-1%29%7D%20%7D%7B3%7D)
=
[Since, i =
]
b).
= ![\frac{10}{2}\pm \frac{\sqrt{-16}}{2}](https://tex.z-dn.net/?f=%5Cfrac%7B10%7D%7B2%7D%5Cpm%20%5Cfrac%7B%5Csqrt%7B-16%7D%7D%7B2%7D)
= ![5\pm \frac{4\sqrt{-1}}{2}](https://tex.z-dn.net/?f=5%5Cpm%20%5Cfrac%7B4%5Csqrt%7B-1%7D%7D%7B2%7D)
= 5 ± 2i [Since, i =
]
c).
= ![-\frac{3}{6}\pm \frac{\sqrt{-144}}{6}](https://tex.z-dn.net/?f=-%5Cfrac%7B3%7D%7B6%7D%5Cpm%20%5Cfrac%7B%5Csqrt%7B-144%7D%7D%7B6%7D)
= ![-\frac{3}{6}\pm \frac{12\sqrt{-1}}{6}](https://tex.z-dn.net/?f=-%5Cfrac%7B3%7D%7B6%7D%5Cpm%20%5Cfrac%7B12%5Csqrt%7B-1%7D%7D%7B6%7D)
= ![-\frac{1}{2}\pm 2\sqrt{-1}](https://tex.z-dn.net/?f=-%5Cfrac%7B1%7D%7B2%7D%5Cpm%202%5Csqrt%7B-1%7D)
=
[Since, i =
]
Answer:
rotation
Step-by-step explanation:
Answer:
3*x-9
Difference means subtraction and times means multiplication!
Hi there, 3+-10=-7 so, -7+5x=13. First, we add -7 to both sides, which gives us 5x=13+7, 13+7=20, so 5x=20. Now, we divide both sides by 5, Therefore, x=4